(3GSJQGJjLjGJ GdEOGQI GdeYQajI aj efXeGJ GdCYeGd (B/s - (3YLdGf, MSjf MSfs ((3YeGf(B: s (3OGQ GKQGA ddfTQ(B, s, 2007)
(3jVe GdGWGQ GdeaGgjej h GdfXQj ddGOGQI GdeYQajI,GdYdGbI Hjf GdeYQaI h GOGA GdefXeI,JMdjd GSJQGJjLjGJ GdGOGQI GdeYQajI, QGS GdeGd GdeYQaj h GdehLhOGJ GdeYQajI, JMdjd GfJGLjI GdYed GdeYQaj hGdJMOjGJ GdJj JhGLg efXeGJ GdGYeGd aj Xd feh GdShb GdeYQajI(B. s
(3HjHdjhZQGajG(B: (3U(B. 207s
Keywords: (3EOGQI GdCYeGds